Edufare for the future precariat: the moral agenda in Australia's 'earning or learning' policy. Issue 1 (2nd January 2017) - Doherty, Catherine
Abstract: This paper considers the educational experience constructed under Australia's policy decision in 2009 to extend compulsory education by requiring that students must be 'earning or learning' till 17 years of age. The discussion draws on an empirical project that explored the moral order operating in classrooms for students retained under this policy in non-academic pathways in high schools and Technical and Further Education colleges across three towns experiencing youth employment stress. It asks how the policy regulating these students' prolonged engagement with formal education plays out in classroom interactions, to what end and to whose benefit. A theoretical lens informed by work by Standing and Wacquant is used to understand the contemporary moment, and work by Durkheim and Bernstein unpacks the moral work implicated in classroom interactions. The analysis describes the light curriculum and the heavy compliance demanded in these 'edufare' programmes then argues that in essence the policy seeks to manage the social risk posed by the future precariat. The conclusion reflects on whether this is an adequate policy response to broad generational changes in fortunes and prospects to which education may not have the answers.